Effect of water deficit and foliar application of amino acids on growth and yield of eggplant irrigated by two drip systems under greenhouse conditions - Basem Rahem Bader; Mohammed Ali Abood; Saad Enad Harfoush Aldulaimy; Shuker Mahmood Hassan Al-Mehmdy; Ghassan Jaafar Hamdi (Agraarteadus, 2020)

(untitled)
Water deficit in semiarid areas limits eggplant (Solanum melongena L.) production and growth indicators. Suitable drip irrigation system and foliar application of amino acids may help overcome water deficit. In this work, the eﬀects of drip irrigation system [Grand flow regulators (GR) and T-Tape], water deficit (50, 75, 100% based on field capacity) and foliar application of amino acids at 0, 100 and 200 mg L–1 on water relation of leaf's, yield and field water use efficiency (WUEf) of eggplant were studied. The experiments were arranged in a split-split plot design within a completely randomized distribution each repeated three times. GR irrigation system treatment produced the highest relative water content (RWC), most yield (TY), WUEf and the lowest of water saturation deficit (WSD) which were 74.71%, 6.50%, 5.97 t ha–1, 2.11 kg m–3 and 23.09%, respectively. The lowest water uptake capacity (WUC) and relative membrane permeability (RMP) was obtained in T-Tape irrigation system treatment (0.43% and 59.45%, respectively). The 100% irrigation level revealed higher RWC (79.32%), WSD (7.38%), most TY (6.93 t ha–1), the least of WSD (18.00%), WUC (0.28%) and RMP (39.40%). The maximum of WUEf (2.37 kg m–3) was obtained from 50% irrigation level. The foliar application of 200 mg L–1 Amino acids rate resulted in significantly maximum RWC (81.50%), WRC (7.19%), TY (6.75 t ha–1) and WUEf (2.51 kg m–3) and least WSD (15.88%), WUC (0.33%), RMP (52.02%). GR drip irrigation system is best for water use efficiency; 200 mg L–1 Amino acids produced the best response for most studied traits.